Changes in Hepatic Blood Flow and Liver Function during Closed Abdominal Hyperthermic Intraperitoneal Chemotherapy following Cytoreduction Surgery. (12th March 2018) - Dupont, Stéphanie; Schiffer, Eduardo R. C.; White, Marion J.; Diaper, John R. A.; Licker, Marc-Joseph; Masouyé, Philippe C.
Abstract : Background . The increase in intra-abdominal pressure (IAP) during closed abdominal hyperthermic intraperitoneal chemotherapy (HIPEC) leads to major haemodynamic changes and potential organ dysfunction. We investigated these effects on hepatic blood flow (HBF) and liver function in patients undergoing HIPEC following cytoreductive surgery and fluid management guided by dynamic preload indices. Methods . In this prospective observational clinical study including 15 consecutive patients, we evaluated HBF by transesophageal echocardiography and liver function by determination of the indocyanine green plasma disappearance rate (ICG-PDR). Friedman's two-way analysis of variance by ranks and Wilcoxon signed-rank test were performed for statistical analysis. Results . During HIPEC, HBF was markedly reduced, resulting in the loss of any pulsatile Doppler flow signal in all but one patient. The ICG-PDR, expressed as median (interquartile 25–75), decreased from 23 (20–30) %/min to 18 (12.5–19) %/min (p < 0.001 ). Despite a generous crystalloid infusion rate (27 (22–35) ml/kg/h), cardiac index decreased during the increased IAP period, inferior vena cava diameter decreased, stroke volume variation and pulse pressure variation increased, lung compliance dropped, and there was an augmentation in plateau pressure. All changes were significant (p < 0.001 ) and reversed to baseline values post HIPEC. Conclusion . Despite optimizing intravenous fluids during closed abdominal HIPEC, we observed a marked decrease in HBF and liver function. Both effects were transient and limited to the period of HIPEC but could influence the choice between closed or open abdominal cavity procedure for HIPEC and should be considered in similar clinical situations of increased IAP.